Communicating About Water in the Floridan Aquifer Region: Part 1—What Do People Know About Water Science? - Sadie Hundemer; Shenara Ramadan (EDIS)
Meaningful engagement by the public in the water decisions that affect their lives requires basic scientific knowledge, such as where their water comes from, the factors that affect quality and availability, and the challenges that influence water supply. A 2020 study suggests that Florida and Georgia residents lack fundamental knowledge about their water resources, including regional water processes, including its challenges, and policies. This is the base information that would enable a person to competently participate in water discussions and make citizen-level voting decisions on topics related to the Floridan aquifer. The knowledge deficits identified in the study are areas on which water communicators can build the public’s water science comprehension and, thereby, support increased public engagement. The findings also suggest the level of water science complexity that the public is equipped to understand.